COMPLEX SIMULATION MODEL OF TRAIN BREAKING-UP PROCESS AT THE HUMPS - Demchenko, E. B. (Science and Transport Progress, 2015)
Purpose. One of the priorities of station sorting complex functioning improvement is the breaking-up process energy consumptions reduction, namely: fuel consumption for train pushing and electric energy consumption for cut braking. In this regard, an effective solution of the problem of energy consumption reduction at breaking-up subsystem requires a comprehensive handling of train pushing and cut rolling down processes. At the same time, the analysis showed that the current task of pushing process improvement and cut rolling down effectiveness increase are solved separately. To solve this problem it is necessary to develop the complex simulation model of train breaking up process at humps. Methodology. Pushing process simulation was done based on adapted under the shunting conditions traction calculations. In addition, the features of shunting locomotives work at the humps were taken into account. In order to realize the current pushing mode the special algorithm of hump locomotive controlling, which along with the safety shunting operation requirements takes into account behavioral factors associated with engineer control actions was applied. This algorithm provides train smooth acceleration and further movement with speed, which is close to the set speed. Hump locomotive fuel consumptions were determined based on the amount of mechanical work performed by locomotive traction. Findings. The simulation model of train pushing process was developed and combined with existing cut rolling down model. Cut initial velocity is determined during simulation process. The obtained initial velocity is used for further cut rolling process modeling. In addition, the modeling resulted in sufficiently accurate determination of the fuel rates consumed for train breaking-up. Originality. The simulation model of train breaking-up process at the humps, which in contrast to the existing models allows reproducing complexly all the elements of this process in detail and evaluate accurately its quality, was improved by the author. Practical value. The developed model can help to determine a rational processing mode of sorting complex. For this purpose, it is appropriate to include the model into the decision support system of dispatching station staff.